The bioenergetics and trophic ecology of leatherback turtles (Dermochelys coriacea) - Wallace, Bryan Patrick (Drexel University, 2005)
Leatherback turtles, Dermochelys coriacea, are critically endangered, long-lived migratory reptiles and are specialist predators for gelatinous prey. Their unique physiological and life history traits make quantification of their energetic requirements and understanding of their trophic ecology crucial to conservation of the species. Using doubly labeled water (DLW) on adult female leatherbacks I obtained the first field metabolic rates (FMRs; 0.20 - 0.74 W kg-1) and water turnover rates (16 - 30% Total Body Water d-1) for free-swimming marine turtles and combined these data with dive information from electronic archival tags to quantify the bioenergetics and diving activity of reproductive adult female leatherback turtles. Internesting leatherback dive durations were consistently shorter than aerobic dive limits calculated from my FMRs, indicating that internesting female leatherbacks spent relatively little energy while active at sea. Energy budget calculations using the FMRs indicated that resource limitation related to the El Niño-Southern Oscillation (ENSO) might lengthen remigration intervals for eastern Pacific leatherbacks as compared to North Atlantic leatherbacks, thus decreasing the eastern Pacific population’s reproductive success and increasing its exposure to risk of incidental fisheries mortality, resulting in plummeting eastern Pacific populations. Analyses of stable carbon and nitrogen stable isotopes ratios (δ13C and δ15N) of leatherback tissues from eastern Pacific and North Atlantic nesting populations revealed that while δ13C signatures were similar between North Atlantic (-19.4‰ ± 1.0‰) and eastern Pacific leatherbacks (-19.1‰ ± 0.7‰), reflecting the pelagic foraging strategy of the species, eastern Pacific leatherback δ15N signatures (15.4‰ ± 1.8‰) was significantly enriched relative to North Atlantic leatherback δ15N signatures (9.8‰ ± 1.5‰). This δ15N discrepancy reflects inter-basin differences in nitrogen cycling regimes and their influence on primary production being transferred through several trophic levels.Combination of FMRs and dive data described the relationship between physiology, environment, and activity, and energy budget calculations and stable isotope analyses demonstrated fundamental differences in marine habitats of eastern Pacific and North Atlantic leatherbacks. Integrated approaches to understanding how physiology, environment, and resource availability interact to constrain animal bioenergetics, and thus, life history can drastically strengthen the efficacy of global initiatives toward conservation of marine biodiversity. Ph.D., Environmental Science -- Drexel University, 2005